Public investment in care services in Turkey: Promoting employment & gender inclusive growth - Kim, Kijong; İlkkaracan, İpek; Kaya, Tolga (Elsevier BV, 2019)
Abstract Recent policy debates on macroeconomic tools to counteract the prolonged global economic recession point to the potential of fiscal policies with appropriate sectoral targets for simultaneously boosting effective demand while alleviating inequalities through employment generation. This paper contributes to the debate by pointing to the social care services sector –in particular early childhood education and care (ECEC) — as an effective target of fiscal spending for robust employment generation and gender inclusive growth. We use a macro-micro simulation model to examine the aggregate and gender employment impact of increasing public expenditures on ECEC services, an underdeveloped sector in Turkey versus physical infrastructure and construction, a common target of stimulatory spending. Our methodological approach combines input-output analysis on aggregate employment effects with a statistical microsimulation approach to assess distributional outcomes. We find that an expansion of ECEC services creates not only significantly more jobs but also does so in a more gender-equitable and fiscally sustainable way than the a construction boom.